Associations Between Defense Styles, Approaches to Learning, and Achievement Among University Students - Karagiannopoulou, Evangelia; Milienos, Fotios S.; Athanasopoulos, Vasileios (Frontiers in Education, 2018)
The present study explores associations between defense styles, approaches to learning, students’ preferences for different types of courses/teaching and achievement. The psychometric properties of the Defense Style Questionnaire (DSQ-40), used for assessing students’ defense styles, are also explored. Participants in this study were undergraduates (N=425) studying in a social science department.The Approaches and Study Skills Inventory for Students (ASSIST) is used for exploring students’ approaches to learning, while Grade Point Average (GPA) measured students’ academic achievement. The study suggests the contribution of defense styles to the Student Learning Research; it reports a mature and an immature learning pattern. Deep and strategic approaches to learning, preferences for classes that support understanding and GPA are associated with a mature defense style, whereas surface approach and preferences for classes that transmit information are associated with immature, image-distorting and neurotic defense styles. Defense styles as well as preferences for different courses appear to act as antecedents of approaches to learning; approaches mediate the effect of defenses and preferences on achievement although defenses have only a small impact. The study also suggests a four factor structure of the DSQ-40 in undergraduates. The findings are discussed in the context of the recent literature.